Promoting the Good Governance by Advancing the Role of Parliamentarians and the Term Offices Limitation (Comparing Nigeria and Indonesia) (Universitas Negeri Semarang, 2022)
In the 21st century new world order, there is growing interest more than ever before in issues related to democracy and good governance around the world. This is a reflection of the increasing acceptance of the fact that democracy and good governance are not a luxury, but a fundamental requirement to achieve sustainable development. Parliament as of the key state institutions in a democratic system of governance have a critical role to play in promoting democracy and good governance. As the democratically elected representatives of the people, parliaments have the honourable task to ensure good government by the people and for the people. In the performance of their key functions of legislation, representation and oversight, parliaments encounter challenges that negatively affect their efforts in promoting democracy and good governance. The paper attempts to discuss the concept of parliamentary governance and the contribution of the parliament in consolidating democracy in Indonesia and Africa. This includes examining how parliaments respond to the growing public pressure for greater involvement, information, accountability and better service delivery to the citizens and the limitation of term offices ans one of the accountability processes. The paper argues that parliamentary governance is the basic parameter in assessing the progress of democracy in a country and concludes that lack of it is the source of poor governance with the attendant political, economic and social problems in a state.